Investment-cash flow sensitivities and capital misallocation - Ek, Chanbora (2019)
This paper directly estimates the effect of financing constraint on capital misallocation. We provide a simple theoretical framework that links the heterogeneity in investment-cash flow sensitivity, a common indicator of financing constraint, to the dispersion of marginal revenue product of capital, a direct measure of allocative inefficiency. Our model shows that the existence of both constrained and unconstrained firms is a sufficient though not necessary condition for capital misallocation. Empirically, we run an error-correction investment model for U.S. Compustat and Chinese manufacturing firms, and for various sub-samples of the Chinese firms. Our estimates on investment-cash flow sensitivities imply a 5% and 15% total factor productivity loss respectively for the balanced and unbalanced panels of Chinese firms. Our identification strategy does not require any monotonic relationship between investment-cash flow sensitivities and severity of financial frictions, thus is not subject to the Kaplan and Zingales critique.